Acupuncture Modulates the Spontaneous Activity and Functional Connectivity of Calcarine in Patients With Chronic Stable Angina Pectoris - Lan, Lei; Yin, Tao; Tian, Zilei; Lan, Ying; Sun, Ruirui; Li, Zhengjie; Jing, Miaomiao; Wen, Qiao; Li, Shenghong; Liang, Fanrong; Zeng, Fang (Frontiers in Molecular Neuroscience, 2022)
Background: Acupuncture is an effective adjunctive therapy for chronic stable angina pectoris (CSAP), while the underlying mechanism is unclear. This study aimed to investigate the central pathophysiology of CSAP and explore the mechanism of different acupoint prescriptions for CSAP from the perspective of brain-heart interaction. Methods: Thirty-seven CSAP patients and sixty-five healthy subjects (HS) were enrolled, and thirty CSAP patients were divided into two acupoint prescriptions groups (Group A: acupoints on the meridian directly related to the Heart; Group B: acupoints on the meridian indirectly related to the Heart). The Magnetic Resonance Imaging data and clinical data were collected at baseline and after treatment. The comparisons of brain spontaneous activity patterns were performed between CSAP patients and HS, as well as between baseline and after treatment in CSAP patients. Then, the changes in resting-state functional connectivity before and after treatment were compared between the two acupoint prescriptions. Results: CSAP patients manifested higher spontaneous activity on the bilateral calcarine, left middle occipital gyrus, right superior temporal gyrus, and right postcentral gyrus. After acupuncture treatment, the spontaneous activity of the left calcarine, left cuneus, and right orbitofrontal gyrus was decreased. The left calcarine was identified as region-of-interest for functional connectivity analysis. Compared with group B, CSAP patients in group A had significantly increased functional connectivity between left calcarine and the left inferior temporal gyrus/cerebellum crus 1, left hippocampus, left thalamus, and left middle cingulate cortex after treatment. thresholds for all comparisons were p < 0.05, Gaussian Random Field corrected. Conclusion: Regulating the aberrant spontaneous activity of the calcarine might be an underlying mechanism of acupuncture for CSAP. The multi-threaded modulation of functional connectivity between calcarine and multiple pain-related brain regions might be a potential mechanism for better efficacy of acupuncture at points on the meridian directly related to the Heart.